Characterization of Copper Entrapment to Polystyrene as an Adsorber for Wastewater Remediation Application - mohd radzi, nur aimi syafika; Agam, Arif (Enhanced Knowledge in Sciences and Technology, 2023)
Among hazardous materials released by industrial activities are heavy metals and the cost to create a cheaper absorber to purify wastewater from industries has become the major trend in research. Due to their simplicity, low cost, high reactivity, low toxicity, and chemical stability, numerous semiconductors such as ZnO, ZnS, CdS, TiO2, MoO3, Ag2O, and Fe2O3 are used to degrade toxic organic pollutants or act as absorbers for heavy metals removal from wastewater, either through photocatalytic processes or chemical reduction. In this research, Expanded Polystyrene (EPS) is used as the base material, trapping Cu nanoparticles (Cu Nps) in absorbing Zn heavy metals in the wastewater. Cu NPs were synthesized by preparing the stock solution of CuSO₄.5H₂O and the same goes for the preparation of Zn synthetic wastewater. As a sample for wastewater, stock solutions of Zn synthetic wastewater were synthesized at concentrations of 10, 20, and 30 mg/l. EPS was synthesized by the nanoprecipitation method by using Tetrahydrofuran (THF) as the reducing agent. The chemical interaction of PS Cu NPS was determined by Fourier Transform Infrared Spectroscopy (FTIR) while the surface morphology of each of the samples was determined by Field Emission Scanning Electron Microscopy (FESEM). UV-Vis was utilized to measure the absorbance value of Zn. The removal of Zn heavy metals was influenced by two parameters: pH value and adsorber adsorbent dose. This paper identifies PS Cu NPs as a potentially useful nanotechnology material capable of removing heavy metals from wastewater remediation applications.